An Assessment of the Energy and Nutritional Value of Menus Delivered by a Catering Company in a Selected Kindergarten in Wrocław and Parental Awareness Regarding Dietary Recommendations - Smolińska, Julia; Książek, Ewelina (Ocena wartości energetycznej i odżywczej jadłospisów dostarczanych przez firmę cateringową w wybranym przedszkolu we Wrocławiu oraz świadomość rodziców dotycząca rekomendacji żywieniowych, 2023)
Objective: The proper nutrition of preschool children is one of the key elements supporting their physical and mental development and intellectual agility. With the increasing awareness of the role of diet in preventing lifestyle diseases, there is a growing need for comprehensive education and the development of healthy eating habits from an early age. In this regard, parents and caregivers face the significant challenge of providing adequate and balanced diets that meet the individual nutritional needs of their children. This study aimed to estimate the energy and nutritional value of decadal menus provided by a catering company in a selected kindergarten in Wrocław. Additionally, a proprietary survey questionnaire assessed parental awareness of nutritional recommendations. Methodology: Forty dietary plans were analysed using the Dieta 6D computer software. The energy value and content of nutritional components, such as protein, fats, carbohydrates, mineral components (calcium, iron), and vitamins (A, C), were estimated in decadal menus for each season. In the second part of the study, parental awareness of nutritional recommendations was assessed. A survey questionnaire was prepared and directed to parents or guardians of preschool-aged children. Results: A qualitative analysis of 10-day dietary allowances showed them as being composed based on the principles of healthy eating, taking into consideration variety, seasonality of products, and diverse cooking techniques. The menus differed in meeting children’s needs for vitamins and mineral components. Regardless of the season, they provided an excessive amount of vitamin A compared to recommended norms, while vitamin C intake exceeded recommended norms in summer. Calcium content was consistently below dietary recommendations for the age group of 4 to 6 years. Only the iron content complied with the norms, regardless of the season. The survey research results indicate that parents of preschool-aged children pay close attention to nutrition in preschool facilities. When acquiring knowledge about the nutrition of 3-6-year-old children, parents rely on information from their relatives and dietitians rather than scientists specialising in children’s nutrition. Unfortunately, regarding knowledge about the dosage of vitamin D, only 35% of parents with higher education knew the appropriate dosage of vitamin D required at this age. Implications and recommendations: The assessment of preschool menus indicated the necessity of changes regarding their composition modifications, including adding legume seeds into the diet and limiting meals containing simple sugars. The knowledge and dietary attitudes of preschool teachers and parents play a significant role in shaping children’s dietary habits. Research has shown that inadequate or excessive intake of nutrients, ‘picky eating’ behaviour, and lack of knowledge about nutrition among teachers and staff are common issues in preschools. Therefore, interventions focusing on improving knowledge and dietary attitudes among teachers and parents are essential.
Nauki Inżynierskie i Technologie = Engineering Sciences and Technologies, 2023, Nr 39, s. 143-160
Keywords: decadal menu plans; nutritional value assessment; child nutrition; dekadowe plany jadłospisów; ocena wartości odżywczej; żywienie dzieci